2007
DOI: 10.1038/sj.emboj.7601844
|View full text |Cite
|
Sign up to set email alerts
|

Sequential steps and checkpoints in the early exocytic compartment during secretory IgM biogenesis

Abstract: The biogenesis of secretory IgM occurs stepwise under stringent quality control, formation of l 2 L 2 preceding polymerization. How is efficiency of IgM secretion coupled to fidelity? We show here that ERp44, a soluble protein involved in thiol-mediated retention, interacts with ERGIC-53. Binding to this hexameric lectin contributes to ERp44 localization in the ER-golgi intermediate compartment. ERp44 and ERGIC-53 increase during B-lymphocyte differentiation, concomitantly with the onset of IgM polymerization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
181
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(188 citation statements)
references
References 43 publications
5
181
0
Order By: Relevance
“…In the crowded environment of an antibodyproducing cell, a sophisticated quality control system is present (27). In the case of IgM, the formation of pentamer/hexamer complexes is stringently controlled by the ERp44/ERGIC53 assembly platform including a thiol retention mechanism via Cys575 (28,29). In addition, it was shown that carbohydrates have an influence on oligomerization (30), particularly the glycan linked to Asn563 in the tp of Cμ4 that interacts with ERp44.…”
Section: Discussionmentioning
confidence: 99%
“…In the crowded environment of an antibodyproducing cell, a sophisticated quality control system is present (27). In the case of IgM, the formation of pentamer/hexamer complexes is stringently controlled by the ERp44/ERGIC53 assembly platform including a thiol retention mechanism via Cys575 (28,29). In addition, it was shown that carbohydrates have an influence on oligomerization (30), particularly the glycan linked to Asn563 in the tp of Cμ4 that interacts with ERp44.…”
Section: Discussionmentioning
confidence: 99%
“…During folding and assembly of the IgM chains, all these ER or ERGIC proteins bind transiently, some shorter and some for longer periods, either simultaneously or in sequence. For example, early in the process, GRP94 acts after BiP (22), by promoting folding of H chains and assembly with L chains to HL ''hemimers,'' whereas much later, ERGIC53 acts after ERp44, when they assist assembly of H 2 L 2 monomers into multimers (25). IgM does mature in the absence of pERp1, but the reduction of IgM secretion on pERp1 down-regulation is impressive for any ER folding factor.…”
Section: Discussionmentioning
confidence: 99%
“…Shimizu et al (14) identified pERp1 as part of this complex. Recently, also ERp44 and ERGIC53 were added to the list of assistants of IgM assembly (25). During folding and assembly of the IgM chains, all these ER or ERGIC proteins bind transiently, some shorter and some for longer periods, either simultaneously or in sequence.…”
Section: Discussionmentioning
confidence: 99%
“…8) Translation is sensitive to redox conditions through Trx interactions and Trx-like domains in elongation initiation factors. 9) Processing of proteins destined for secretion or insertion in the plasma membrane, such as VCAM-1, ICAM-1, and E-selectin often require redox-dependent processing in the secretory pathway (7,24). 10) Function of cell surface receptors is dependent on redox-sensitive Cys in integrins, cytoskeletal proteins (e.g., actin, cofilins), and Cys-rich regions in the receptors.…”
Section: Steady-state E H Of Cys Residues In Proteinsmentioning
confidence: 99%
“…Sites sensitive to changes in thiol-disulfide redox state are indicated by an "-SH/-SS-" balance. A: in early proinflammatory signaling in endothelial cells, redox-dependent signaling includes 1) extracellular Cys/CySS redox potential (55) (109); 9) processing of proteins in the secretory pathway (7,24); and 10) cytoskeletal/ surface structure (33,140,187). B: in receptormediated signaling, redox-sensitive steps include 1) metalloprotease-sensitive growth factor release (134); 2) metalloprotease-sensitive degradation of growth factor inhibitor (51); 3) redox-dependent activation of receptors (31, 94); 4) H2O2-dependent Ca 2ϩ influx and Nox-5 activation (40); 5) active-site Cys residues required for phosphatase activity [PTP1B, SHP2, PTen; (39)]; 6) Ras activity (3); 7) Src activity (48); 8) H2O2 metabolism; 9) lipoxygenase activity (42); 10) LPS activation of cytoplasmic and mitochondrial H2O2 production through Toll-like receptor 4 [TLR4 (77,139)] (42,77,139).…”
Section: Oxidative Stress As a Disruption Of Redox Signaling And Controlmentioning
confidence: 99%